Epigenetic epidemiology: Promises for public health research. (21st January 2014) - Bakulski, Kelly M.; Fallin, M. Daniele; O'Hagan, Heather; Tang, Winnie
<x xml:space="preserve">Abstract</x> Epigenetic changes underlie developmental and age related biology. Promising epidemiologic research implicates epigenetics in disease risk and progression, and suggests epigenetic status depends on environmental risks as well as genetic predisposition. Epigenetics may represent a mechanistic link between environmental exposures, or genetics, and many common diseases, or may simply provide a quantitative biomarker for exposure or disease for areas of epidemiology currently lacking such measures. This great promise is balanced by issues related to study design, measurement tools, statistical methods, and biological interpretation that must be given careful consideration in an epidemiologic setting. This article describes the promises and challenges for epigenetic epidemiology, and suggests directions to advance this emerging area of molecular epidemiology. Environ. Mol. Mutagen. 55:171–183, 2014. © 2014 Wiley Periodicals, Inc.